Investigating wisdom: Call for research. Issue 1 (18th October 2019) - Allen, Jeff; Khader, Malak; Rosellini, Amy
ABSTRACT: This study aims to address the gap in understanding "wisdom" as it relates to Data, Information, Knowledge, Wisdom (DIKW) Model/Hierarchy and the information science discipline. Disciplines like data science, information science, and knowledge management study wisdom without defining it. This study identifies the definition of the term wisdom within the information science discipline.